Probiotics and broiler growth performance: a meta-analysis of randomised controlled trials - Blajman, Jesica E.; Frizzo, Laureano Sebastian; Zbrun, María Virginia; Astesana, Diego Martín; Fusari, Marcia Lucia; Soto, Lorena Paola; Rosmini, Marcelo Raúl; Signorini, Marcelo (2018)
1. The aim of this meta-analysis was to investigate the effects of probiotics on the growth performance of broilers. PubMed, Scopus and Scholar Google databases were searched in all languages from 1980 to 2012. The studies in the meta-analysis were only selected if they were randomised and controlled experiments using broilers without apparent disease and the results were published in peer-reviewed journals. 2. A total of 48 and 46 studies were included to assess probiotic effects on body weight gain (BWG) and feed efficiency (FE), respectively. Probiotics increased BWG compared to controls (SMD = 0.661, 95% CI 0.499 to 0.822) and improved FE (SMD = − 0.281, 95% CI −0.404 to −0.157) in the pooled standardised mean difference random effect model, considering the source of heterogeneity and publication biases. However, there are evidences of publication bias and heterogeneity, so the results of this meta-analysis should be considered with caution. Applying the Duval and Tweedie’s trim-and-fill methods, the adjusted value for BWG was 0.0594 (95% CI −0.122 to 0.242), and the adjusted value for FE did not show any modifications. 3. The meta-analysis showed that application of probiotics via water resulted in greater BGW and FE than administration through the feed. The effect was not related to the use of mono-strain or multi-strain probiotics, although it may depend on the strain used. The number of broilers and the duration of the experiments had an impact on the outcomes. 4. Additional studies should be conducted with the aim to identify the covariates which can explain the differences in the estimated effect sizes.